On Bautin Bifurcation in a Monetary Dynamic Model - Kyseľová, Katarína; Zimka, Rudolf (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
In the paper a two-dimensional dynamic model of Asada (2011) describing the development of nominal rate of interest and expected rate of inflation is investigated. There are found conditions under which Bautin bifurcation (generalized Hopf bifurcation) arises. This kind of bifurcation enables the existence of so called corridor stability, when around the stable equilibrium two cycles emerge, the inner one which is unstable and the outer one which is stable. Numerical simulations of the model illustrating the achieved results are presented
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 259-274
Keywords: dynamic model; equilibrium; stability; limit cycles